The economics of diamond projects in the Canadian Arctic (bbedb282-085a-4c62-8fa2-4245fef0430a) - W. Bullen (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
A hypothetical economic model has been developed for diamond projects in the Canadian Arctic using data from recent exploration and mining projects. The model reflects economic conditions applicable to the diamond mining industry in the Canadian Arctic at the present time. The economic model captures pre-production expenditures, production data, and post-production costs. Before- and after-tax cash flows are derived from the data along with the relevant economic criteria. From the corporate perspective, the model provides guidance concerning the minimum size and/or in situ value per tonne requirements of targets being sought in order to ensure economic success and predict exploration and development expenditures. From the government perspective, the model provides an indication of income and mining tax revenues that can be expected from a particular diamond project. The model shows, on average, diamond projects in the Canadian Arctic are expensive to explore for and develop, but are economically robust under the present conditions. They generate great economic return for mining companies and significant amounts of tax revenue for governments. The fact that diamonds can be transported directly from the minesite by air makes them particularly attractive targets for mining companies that operate in the Canadian Arctic.